Local contact formation during sliding on soft adhesive surfaces with complex microstructuring. (November 2021) - Kumar, Charchit; Speck, Thomas; Le Houérou, Vincent
Abstract: Friction on biological-like micro-structured surfaces has been investigated. Using a bio-replication technique, complex surface morphologies found in plant leaves were transferred onto viscoelastic substrates. A nano-indenter was modified, permitting in-situ real contact junctions visualisation. Effects of applied normal load and sliding speed on the friction response were evaluated. All four surfaces demonstrated a decrease in the friction coefficient (but dissimilar behaviors) with increasing normal load. In-situ videos revealed different contact formation under shearing, which originated from the specific surface topographies. An increase in friction coefficient with rising sliding speed was found out. This speed-dependent friction response was qualitatively correlated with material loss factor and the different friction incremental rates were discussed in the light of strain localisation in the confined topographies. Highlights: Systematic investigation of sliding friction carried out on transparent elastomeric replicas of natural plant leaves. Contact system inspired from the insect interactions with plant leaves consisting of different topographies. A nano-indenter system was coupled with an original technique for in- situ visualization of real contact formation. Reports of sliding dynamics and friction force characteristics regarding the applied normal load and the sliding speed. Promising insight in order to design sustainable (bio-inspired) and friction-tuneable technical surfaces.